CHARACTERIZATION OF BACTERIAL ISOLATES FROM DETOXIFICATION BIOTREATMENT OF 2,4,6-TRINITROTOLUENE CONTAMINATED WASTEWATER - Hà, Đặng Thị Cẩm (Vietnam Journal of Biotechnology, 2011)
Aerobic bacteria play a very important role in biodegradation and detoxification of wastewater contaminated 2,4,6-trinifrotoluene (TNT). Decomposition process depends on the presence of infracellular and/or exfracellular enzymes. Two bacterial sfrains BQNR and BQNT2 were isolated from explosive wastewater containing 1600 ppm Tl^IT showed ability in production of exfracellular enzyme. In mineral salt medium containing 100 ppm TNT inoculated with BQNR sfrain, activity of peroxidase enzymes were determined at different level, 52,5 U/l for LiP and 251,2 U/l for MnP. Strain BQNT2 produced LiP and laccase with activity 24,9 U/l and 15 U/l, respectively. The full sequence of BQNR 16S rRNA gene has a high homology to Pseudomonas stutzeri species and it was classified as Pseudomonas sp. BQNR. The 16S rRNA gene sequence of BQNT2 showed high similarity to Achromobacter xylosoxidans and named as Achrombacter fsp. BQNT2. These sequences of two BQNR and BQNT2 examined strains were deposited in the GenBank with , accession number EU741649 and FJl79539, respectively. In shaking with mineral salt medium containing 600 . ppm TNT, at 37°C bacterium BQNR showed best growth. In cultural medium BQNR strain removed 99,35% * TNT with initial concentration 100 ppm after 5 days.